The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.amepre.2013.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and the Strength of Evidence of U.S. Alcohol Control Policies

Abstract: Background Public policy can limit alcohol consumption and its associated harms, but no direct comparison of the relative efficacy of alcohol control policies exists for the U.S. Purpose To identify alcohol control policies and develop quantitative ratings of their efficacy and strength of evidence. Methods In 2010, a Delphi panel of ten U.S. alcohol policy experts identified and rated the efficacy of alcohol control policies for reducing binge drinking and alcohol-impaired driving among both the general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 26 publications
4
98
0
2
Order By: Relevance
“…The average price elasticities reported here imply that reducing alcohol consumption through price or tax increases will be less effective or more costly than previously suggested or claimed [35][36][37][38]. Cumulative average price elasticities are 28-29% smaller than "consensus" estimates, with a price inelastic demand for all three beverages (-0.30 to -0.55) and total alcohol (-0.50).…”
Section: Discussionmentioning
confidence: 43%
“…The average price elasticities reported here imply that reducing alcohol consumption through price or tax increases will be less effective or more costly than previously suggested or claimed [35][36][37][38]. Cumulative average price elasticities are 28-29% smaller than "consensus" estimates, with a price inelastic demand for all three beverages (-0.30 to -0.55) and total alcohol (-0.50).…”
Section: Discussionmentioning
confidence: 43%
“…Brand et al's (2007) comparative analysis of alcohol control policies across 30 countries found that strong alcohol control policy implementation was associated with reduced per capita consumption. A recent U.S.-based project (Naimi et al, 2014;Nelson et al, 2013) used a ranking approach that confirmed the main finding by Brand et al (2007), and Carragher, Byrnes, Doran, and Shakeshaft (2014) assessed the adequacy of 16 national alcohol policies in nine areas in the Western Pacific.…”
Section: Background and Rationalementioning
confidence: 64%
“…37 Los incrementos en los impuestos también son un enfoque altamente costo-efectivo para reducir el consumo total del alcohol y el número de episodios de consumo excesivo de alcohol, sobre todo entre los jóvenes. 38 Los impuestos y los aumentos en el precio necesitan ser sustanciales para lograr los cambios deseados en el consumo. La imposición tributaria a las calorías vacías, como las bebidas endulzadas con azúcar, puede reducir la prevalencia de la obesidad y generar ingresos públi-cos. 39 Los subsidios a los energéticos como el carbón, la gasolina y el diésel están muy generalizados y alientan el consumo excesivo de energéticos y la producción de contaminación atmosférica por materias y partículas, y por otros contaminantes que causan infecciones de las vías respiratorias bajas en los niños, y cánceres, enfermedad coronaria y enfermedad pulmonar obstructiva crónica en los adultos.…”
Section: Impuestos Y Subsidiosunclassified